The Berenstain bears and too much pressure - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1992)
Members of the Bear family commit themselves to so many time-consuming activities that the resulting stress brings on a crisis and makes them admit that there are only so many hours in a day.
Keywords: Time -- Fiction; Stress (Psychology) -- Fiction; Bears -- Fiction